2019
DOI: 10.1111/jgh.14644
|View full text |Cite
|
Sign up to set email alerts
|

Searching for the link; mechanisms underlying liver regeneration and recurrence of colorectal liver metastasis post partial hepatectomy

Abstract: Despite excellent treatment of primary colorectal cancer, the majority of deaths occur as a result of metastasis to the liver. Recent population studies have estimated that one quarter of patients with colorectal cancer will incur synchronous or metachronous colorectal liver metastasis. However, only one quarter of these patients will be eligible for potentially curative resection. Tumor recurrence occurs in reportedly 60% of patients undergoing hepatic resection, and the majority of intrahepatic recurrence oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 88 publications
1
19
0
Order By: Relevance
“…Down-regulation of c-myc is likely to be one mechanism through which captopril and other RASi are capable of attenuating tumor growth and progression. RASi are commonly used to treat hypertension and cardiac failure; however, they also have a wide range of effects which are not limited to the cardiovascular system [ 29 , 48 ]. RASi have established roles in multiple processes influencing cancer progression, including angiogenesis, extracellular matrix remodeling, cellular proliferation, EMT and immunomodulation [ 27 , 29 , 30 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Down-regulation of c-myc is likely to be one mechanism through which captopril and other RASi are capable of attenuating tumor growth and progression. RASi are commonly used to treat hypertension and cardiac failure; however, they also have a wide range of effects which are not limited to the cardiovascular system [ 29 , 48 ]. RASi have established roles in multiple processes influencing cancer progression, including angiogenesis, extracellular matrix remodeling, cellular proliferation, EMT and immunomodulation [ 27 , 29 , 30 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…RASi are commonly used to treat hypertension and cardiac failure; however, they also have a wide range of effects which are not limited to the cardiovascular system [ 29 , 48 ]. RASi have established roles in multiple processes influencing cancer progression, including angiogenesis, extracellular matrix remodeling, cellular proliferation, EMT and immunomodulation [ 27 , 29 , 30 , 48 ]. Recently, it has been demonstrated that RAS genes are also down-stream targets of Wnt signaling, and that blocking Wnt signaling down-regulates the expression of RAS genes, reversing the clinical effects of renal fibrosis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nivolumab led to shorter OS in patients with previously treated advanced squamous non-small-cell lung cancer with ECOG PS 2 vs. 0-1 (25). Multiple overlapping signaling pathways are involved in liver regeneration and hepatocarcinogenesis, including Wnt/β-catenin and Notch (26). These signaling pathways play an important role in regulating the crosstalk between the different compartments of the tumor microenvironment (27,28), which has been observed to correlate with the response to checkpoint blocking antibodies (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they may explain the high incidence of cancers that arise in the liver, representing a global health burden, which may result from preserved regenerative competence 24 . Clinical data indicate potentially deleterious effects of liver regeneration, induced by therapeutic interventions such as live-donor liver transplantation and liver resection, on tumor biology and outcomes in the context of primary liver cancer 25 and metastatic tumors 26 . Our findings may provide a mechanistic basis of these clinical observations.…”
Section: Discussionmentioning
confidence: 99%